To what extent do prescriptive decision-making models comprehend policy-making in the Third World with reference to South African environmental policy-making? - Damon, Irvan Clinton Clive (Department of Political Studies, 2021)
Policy research and analysis is a complex and dynamic field of study and practice. This study explores the field i l l terms of assessing the utility of contemporary policy techniques ill the intematiollal context and the implications thereof for environmental policy-making in South Africa. More recently, the politics of envirollmental policymaking has emerged as a major issue 011 both the agendas of the developed and developing nations. As underscored by the seminal Rio Earth Summit of 1992 the e11viro11melil is probably the most pressing challenge facing tile globe in the new millennium. Addressing and prioritising these policy issues may require radical policy shifts. However, this study shows that policy conditionalities prevailing i l l the more industrialised nations have been developed in a different context and may therefore be irrelevant and of limited utility to less developed nations, forcing the latter to subvert the conventional policy cycle. Specifically, this study has explored the context of environmental policy-making in South Africa and extrapolated essential policy proci!dures and elements for its environmental policy-making along the policy-making continuum. In addition, an over-arching framework of sustainable development must support environmental policy development in South Africa. International experience regarding the emerging sustainability paradigm and its relevance for South African policy development is paramount if it is not to lag global environmental policy innovations and developments. Sustainability should emerge as a key organising principle for debate around policy content and structure with the imperative of responding to local policy conditionalities and priorities. As long as South Africa and many developing nations employ industrialised policy techniques, its policy processes and principles will lag effective and context specific policy research and development.